Рублев: биография отдельного лица / Валерий Сергеев - Сергеев Валерий Николаевич (Жизнь замечательных людей, 1986)
Экземпляры: Ф. 4 (20210519) / Инвентарный номер: 16183 / Сис.шифр: 85.143(2Р=Рус)3-8 Рублев / Авт.знак: С32 / ГРНТИ: 18 / ББК: 85.143(2Р=Рус)3-8 Рублев 446.5